Influência da propaganda nos hábitos alimentares: análise de conteúdo de comerciais de alimentos da televisão - Santos, Silvana Lopes dos (2007)
Food advertising and it effect on the food choices has been the target of frequent debates, being attributed to a great part of the responsibility for the problems of bad feeding of the population. Such situation has led to government initiatives with the aim to discipline the food advertising, mainly those destined to children. These initiatives can have important consequences on the promotion strategies of the food sector. The present work had as main objective to investigate the frequency and content of the food commercials on television, considering the strategies adopted in relation to the characteristics of the message, the food, the consumer and the appeals, as well as the execution or not of ethical norms of advertising. Therefore, the programming of three open TV channels was recorded during the morning, afternoon and night at preestablished schedules and then used in the content analysis. The results pointed to the prevalence of food commercials in the morning mainly for children advertising mostly products rich in sugar and fat. It was verified that the messages are fundamentally affectionate, with emphasis on the flavor of the food and the pleasure with little reference to the nutritional aspects and health. Great part of the commercials also presented debatable elements regarding to the ethics. At the end of the work, considerations are made about the need of the analysis of the food choice in a wider context, considering the advertising just one of the influence variables. It is considered that only joint actions of the public and private sector are capable to aid in the promotion of healthier food habits.